Middle-School Students’ Perceptions of History of Science - Muhammet Emin Mısır; Onur Adıgüzel (Sakarya University Journal of Education)
This study aims to investigate middle school students’ perceptions of history of science. The participants were a total of 140 students who studied at 5th, 6th, 7th and 8th middle school grade levels. A Word-Association-Test (WAT) was used to collect data. After data collection, frequencies of response-words were determined. By using cut-point technique, concept webs were drawn. According to the findings, the most different response-words were gathered from the 5th graders, and the least different response-words were gathered from the 8th graders. Participants generally associated the history of science concept with the scientists who made inventions. Besides that, students in the lower grades gave the most different response-words while 8th graders generally associated the concept with the subjects in the science curriculum.